Leadership Styles and Financial management of Family Businesses : Case Studies - Umi nandiroh; Sudarmiatin Sudarmiatin; Agus Hermawan (CV. AFDIFAL MAJU BERKAH, 2023)
This case study examines the relationship between leadership style and financial management in family businesses. Family businesses are unique in terms of their ownership and management structure, with family members often acting as both owners and managers. Therefore, leadership styles play an important role in the financial management of these businesses. This case study examines various leadership styles, including transformational, transactional and paternalistic leadership, and how they influence financial management decisions such as investment, risk-taking and financial performance. The case study, conducted in the Krupuk Rambak Mojokerto MSME community, also explores the role of family dynamics, succession planning and corporate governance in shaping the leadership styles and financial management of family businesses. Overall, the results of the literature review suggest that a combination of transformational and transactional leadership styles, coupled with effective family communication and governance structures, can result in better financial performance in family businesses. However, further research is needed to fully understand the complex interactions between leadership styles, family dynamics and financial management in family businesses.